1994
DOI: 10.1017/s0033822200014521
|View full text |Cite
|
Sign up to set email alerts
|

Human Settlements and the Last Deglaciation in the French Alps

Abstract: According to most geological and geomorphological studies, the maximal advance of the Würmian glaciers in the French Alps occurred at least before 40 ka bp and cannot be dated by 14C. Scientists believed that this dating method could be used for dating the last glacial advance and late deglaciation in the region. The scarce and scattered 14C dating results available from geological samples do not confirm an early (ca. 18 or 20 ka bp) age for the total cooling of the ice nor do they prove that residual ice shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…The non-diamagnetic properties of the limestones are almost completely dominated by goethite, and the marls contain iron-bearing paramagnetic minerals and goethite (Hu, 1997). Rissian and Würmian glaciers (Evin et al, 1994) deposited at least two types of till: one contains abundant schist erratics derived from the inner Alps and is dominated by paramagnetic minerals with low concentrations of primary ferrimagnetic minerals (Hu, 1997); the other is composed of limestones and marls considered to be of local origin (Beck et al, 1996;Hu, 1997;Hu et al, 2001). Early magnetic and Mössbauer studies showed that many of the surface soils in the well-drained parts of the catchment are relatively rich in fine-grained secondary ferrimagnetic minerals (SFMs) produced by pedogenic enhancement mechanisms (Dearing, 1979;Longworth et al, 1979;Dearing et al, 1996).…”
Section: Site Descriptionmentioning
confidence: 99%
“…The non-diamagnetic properties of the limestones are almost completely dominated by goethite, and the marls contain iron-bearing paramagnetic minerals and goethite (Hu, 1997). Rissian and Würmian glaciers (Evin et al, 1994) deposited at least two types of till: one contains abundant schist erratics derived from the inner Alps and is dominated by paramagnetic minerals with low concentrations of primary ferrimagnetic minerals (Hu, 1997); the other is composed of limestones and marls considered to be of local origin (Beck et al, 1996;Hu, 1997;Hu et al, 2001). Early magnetic and Mössbauer studies showed that many of the surface soils in the well-drained parts of the catchment are relatively rich in fine-grained secondary ferrimagnetic minerals (SFMs) produced by pedogenic enhancement mechanisms (Dearing, 1979;Longworth et al, 1979;Dearing et al, 1996).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Significant climatic events occurred in the beginning of the eighth millennium BC in Europe that are responsible for profound changes in the distribution of natural habitats and ecological niches (Guerreschi, 1992;Evin et al, 1994;Broglio and Lanzinger, 1996;Davis et al, 2003;Tinner and Theurillat, 2003;Jalut, 2005;Aceti, 2006;Brugiapaglia, 2007;Badino et al, 2010;Pini et al, 2011). These climatic features certainly conditioned the settlement choices and subsistence strategies of Mesolithic groups (Kozlowski, 1973;Bagolini, 1980;Broglio, 1980;Angelucci, 1997;Guerreschi, 1998).…”
Section: Mesolithic Human Settlements On the Southern Slope Of The Alpsmentioning
confidence: 99%
“…Exposures crossed by the 3 rivers include primarily limestone, dolomitic limestone, and marl of Jurassic and Cretaceous age ( Figure 4A). Late Pleistocene (primarily Würmian) tills (EVIN et al, 1994;NICOUD and MANALT, 2001), fluvio-glacial and lacustrine deposits, and slope scree are also locally important in the southern drainage basin and lake margin ( Figures 4A, 5A-C).…”
Section: Geological and Geographic Considerationsmentioning
confidence: 99%
“…Currently, this is no longer the case. As a result of human modification, especially during the past few centuries (CIIAVOUTIKR, 1977;EVIN et al, 1994;BUII.LIT et al, 1997;NEGREL et al, 1997;BEARING, 2000), the rivers are almost completely confined along their lower stretches ( Figure 5F), and flow from 3 separate, but proximal, source areas directly to the delta and lake shore (Figure 2). Sediment remains confined in each channel as it crosses the Bou du Lac, with records of only minor overbanlc deposition and flooding between the base of deeply incised river valleys and southern lake margin (Figures IB,2A,B).…”
Section: Introductionmentioning
confidence: 99%